تَوظيف المنطق الصُّوري في الإسلام - عناد, علي جبار (Al-Adab Journal, 2019)
Our research is entitled (The Employment of Logic in Islam). It explores the philosophers, speakers, and faqihs' treatment of the employment of logic by ways of the cognitive means of criticism, analysis, and exploration. This is done to come up with a philosophical or ideological position concerning the significance of using it as a mental tool. My approach in this study is an analytical, historical approach to illustrate one of the problems in Islamic thought because of which Islamic philosophers were considered infidels.Along with the introduction, I have divided my study into five sections, which are: introduction of logic as a term, the Islamic-Greek logical identification, the employment of logic philosophically, rejection of logic employment, contemporary analytical Islamic attitudes, and a conclusion with the most significant findings. The visual logic which we study goes back to Aristotle who refined and classified it. Muslims during the Abbasid age translated it to aid them in induction, measurement and definition as a mental tool, especially after opening up to other nations. Its employment and translation were related to religious, cognitive cases and political ideology. Its significant in sciences emerged with Al-Farabi and Ibn Sina, and Ibn Hazm Al-Andalusy. Among the philosophers who deemed it a must to learn are Al-Ghazali and Ibn Rushd. Among the most famous of those who rejected it were such faqihs, speakers sophists, and linguists as Ibn Taymea, Al-Noykhti, Al-Shahrazory (known as Ibn Salah), Abu Saeed Al-Serafi, and Abu Al-Naja Al-Faridh.